Engineering of Sn–porphyrin networks on the silica surface: sensing of nitrophenols in water1. Issue 42 (25th May 2015) - Ko, Ju Hong; Moon, Jong Hun; Kang, Narae; Park, Joon Hyun; Shin, Hee-Won; Park, Nojin; Kang, Sungah; Lee, Sang Moon; Kim, Hae Jin; Ahn, Tae Kyu; Lee, Jin Yong; Son, Seung Uk
<x xml:space="preserve">Abstract</x> Sn–porphyrin networks were engineered on the silica surface using the TLC plate. The resultant system showed emission-based selective and efficient sensing performance toward nitrophenols in water.